The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acs.nanolett.8b04666
|View full text |Cite
|
Sign up to set email alerts
|

Nanocavity-Enhanced Giant Stimulated Raman Scattering in Si Nanowires in the Visible Light Region

Abstract: Silicon photonics has been a very active area of research especially in the past two decades in order to meet the ever-increasing demand for more computational power and faster device speeds and their natural compatibility with complementary metal-oxide semiconductor. In order to develop Si as a useful photonics material, essential photonic components such as light sources, waveguides, wavelength convertors, modulators, and detectors need to be developed and integrated. However, due to the indirect electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 32 publications
(50 reference statements)
3
18
0
1
Order By: Relevance
“…for any of the measurements that may reflect formation of stronger photon–phonon polaritons and/or photon dressed states. In fact, as demonstrated in one of our earlier works even at much higher pumping powers when stimulated Raman scattering was observed, no significant changes in the Raman spectra were observed that may indicate formation of phonon–photon hybrid states. The detailed balance is also not being violated as the system is in a quasiequilibrium state while being pumped by light and, depending on the cavity modes, produces a specific response.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…for any of the measurements that may reflect formation of stronger photon–phonon polaritons and/or photon dressed states. In fact, as demonstrated in one of our earlier works even at much higher pumping powers when stimulated Raman scattering was observed, no significant changes in the Raman spectra were observed that may indicate formation of phonon–photon hybrid states. The detailed balance is also not being violated as the system is in a quasiequilibrium state while being pumped by light and, depending on the cavity modes, produces a specific response.…”
supporting
confidence: 62%
“…13 In addition we have also shown bright white light emission in the Si nanowire integrated with plasmonic cavities even though bulk Si does not emit light because of its indirect band gap. 14,15 Recently, we also demonstrated stimulated Raman scattering in the visible wavelength range in Si nanowires for the first time, 16 which is promising for fabricating nanoscale monolithic Raman lasers. Raman scattering is the process of inelastic scattering of photons from phonons in the ground or excited state which leads to generation or annihilation of phonons via Stokes or anti-Stokes scattering resulting in emission of a photon of slightly lower or higher energy.…”
mentioning
confidence: 99%
“…Moreover, we have revealed bistability regime in the optical heating at intensity around 1 mW/𝜇m 2 . Our results are also helpful for resolving the thermal challenges for all-dielectric resonator-based photonic devices [39], Raman microlasers [40,41], and nanoscale photo-thermal chemistry and sensing [42][43][44]. As an outlook, we believe that the developed bistability approach is quite universal and can be further applied not only for various types of nonlinearities based on Kerr effect [45,46], electron-hole plasma generation [32,33,47] and excitonic effects [48][49][50].…”
Section: Discussionmentioning
confidence: 83%
“…In reference [109], Agarwal et al reported a strong SRS and very high Raman gain in optical cavities made of Si nanowire of various diameters in the visible region [109]. The authors evaluated by electromagnetic calculations an enhancement of the Raman gain coefficient of Si nanowire by a factor greater than 10 6 at 532 nm excitation with respect to the gain value at the 1.55 µm wavelength reported in literature [56], even though the losses are 10 8 higher at 532 nm.…”
Section: Raman Laser In Nanophotonicsmentioning
confidence: 96%